2017
DOI: 10.1016/j.plaphy.2016.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of engineered nanomaterials to plants: Insights into the physiological and biochemical responses-A review

Abstract: Recent investigations show that carbon-based and metal-based engineered nanomaterials (ENMs), components of consumer goods and agricultural products, have the potential to build up in sediments and biosolid-amended agricultural soils. In addition, reports indicate that both carbon-based and metal-based ENMs affect plants differently at the physiological, biochemical, nutritional, and genetic levels. The toxicity threshold is species-dependent and responses to ENMs are driven by a series of factors including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
161
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(183 citation statements)
references
References 234 publications
4
161
2
3
Order By: Relevance
“…Nanoparticles are extremely reactive and are able to pass though the cell membrane [19,23]. Iron oxides and their aggregates cling to the negatively charge cell surface due to electrostatic adhesion [34]. This blocking effect of NPs inhibits sufficient water uptake [37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles are extremely reactive and are able to pass though the cell membrane [19,23]. Iron oxides and their aggregates cling to the negatively charge cell surface due to electrostatic adhesion [34]. This blocking effect of NPs inhibits sufficient water uptake [37].…”
Section: Resultsmentioning
confidence: 99%
“…Many aspects of 4-500 nm Fe NPs influence on plants were studied, but there is no prominent information about Fe 3 O 4 NPs genotoxicity in plants [34]. Therefore, the aim of present study was to detect the iron oxide NPs in flax cells and to investigate the impact of different concentrations of Fe 3 O 4 nanoparticles on explants and calluses of Linum usitatissimum L.…”
Section: +mentioning
confidence: 98%
“…Different concentration of same nanoparticles elicits different effects on plant systems; i.e., low concentrations of nanoparticles may not show any adverse effect on plant, but higher concentrations may cause positive or negative effects on plants (Thuesombat et al 2014). Very recently, Zuverza-Mena et al (2016) suggested that both TiO 2 and ZnO have positive or negative phytotoxic effect. Boonyanitipong et al (2011) reported that ZnO nanoparticles inhibit the root length and reduce the number of roots.…”
Section: Introductionmentioning
confidence: 99%
“…This period seems to be still small to clarify all the aspects of the problem as required by the biosafety principles but sufficient for some preliminary principal conclusions. The data obtained indicate both positive and negative effects of metal nanoparticles on plants [98]. Factors that undoubtedly determine the processes of intracellular penetration of nanoparticles are their chemical nature, size, shape, surface charge, and dose.…”
Section: The Effects Of Noble Metal Nanoparticles On Plantsmentioning
confidence: 89%